Are Chinese and German Children Taxonomic, Thematic, or Shape Biased? Influence of Classifiers and Cultural Contexts - Imai, Mutsumi; Saalbach, Henrik; Stern, Elsbeth (Frontiers in Psychology, 2010)
This paper explores the effect of classifiers on young children’s conceptual structures. For this purpose we studied Mandarin Chinese- and German-speaking three- and five-year-olds on non-lexical classification, novel-noun label extension and inductive inference of novel properties. Some effect of the classifier system was found in Chinese children, but this effect was observed only in a non-lexical categorization task. In the label extension and property generalization tasks, children of the two language groups show strikingly similar behavior. The implications of the results for theories of the relation between language and thought as well as cultural influence on thought are discussed.